ANALISIS PENGARUH PENGGUNAAN SOSIAL MEDIA, TEKNOLOGI INFORMASI, DAN MINAT BERWIRAUSAHA TERHADAP ENTREPRENEURSHIP - Wiyarno; Erna Apriani; Indra Permana; Fachrial Banyu Asmoro (POLITEKNIK LP3I JAKARTA, 2024)
Entrepreneurship is an important idea in supporting the independence of the community to reduce the current unemployment rate, the fact in the field that the level of entrepreneurship is still very low in supporting national economic independence, especially in the younger generation who focus after finishing school and college enter the world of work not entrepreneurship, from this phenomenon, more in-depth research is needed related to the factors that influence entrepreneurship. The purpose of this study was to analyze social media factors, information technology, and young people's entrepreneurial interest in entrepreneurship. The research sample used a saturated sample, namely 130 Pelita bangsa university student respondents. The research method uses descriptive and inferential statistics with a quantitative approach, the data analysis used is multiple linear regression analysis. The results showed that social media variables and entrepreneurial interest had a significant effect with a positive direction on entrepreneurship, while information technology variables had no effect on entrepreneurship.